Triterpenoids-templated self-assembly nanosystem for biomimetic delivery of CRISPR/Cas9 based on the synergy of TLR-2 and ICB to enhance HCC immunotherapy - Bing-Chen Zhang; Chun-Mei Lai; Bang-Yue Luo; Jing-Wei Shao (Elsevier, 2024)
Combination immunotherapy has shown promising potential for enhancing the objective response rate compared to immune checkpoint blockade (ICB) monotherapy. However, combination therapy with multi-drugs is limited by the different properties of the agents and inconsistent synergistic targeted delivery. Herein, based on a universal triterpene template and the anticancer active agent ursolic acid (UA), a cytomembrane-coated biomimetic delivery nanoplatform (UR@M) prepared by the self-assembly of a PD-L1 targeted CRISPR/Cas9 system and UA was designed for hepatocellular carcinoma (HCC) treatment. UR@M showed enhanced tumor accumulation in vivo with homologous tumor targeting, and CRISPR in the nanosystem exhibited potent gene-editing efficiency of 76.53% in vitro and 62.42% in vivo with no off-target effects. UA activated the natural immune system through the TLR-2-MyD88-TRAF6 pathway, which synergistically enhanced the proliferation of natural killer cells and dendritic cells and realized excellent immune cytotoxic T cell infiltration by combining with the ICB of PD-L1. The strategy of work along both lines based on innate immune and adaptive immunity displayed a significant effect in tumor regression. Overall, the UA-templated strategy "killed three birds with one stone" by establishing a self-assembly nanosystem, inducing tumor cell death, and promoting synergistic immunostimulation for HCC treatment.